Optimization of Generation Interval in a Selection Plan for Palas Meat Line - Răzvan Popa; Dana Popa; Marius Maftei; Livia Vidu; Dorel Dronca; Mihaela Ivancia; Georgeta Diniţă; Carmen Nicolae (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of the paper work is to optimize the generation interval in a selection plan, according to model developed by Colburn (1961), which will be proposed to be applied for live weight and traits associated with carcass and meat quality improvement in Palas Meat Line. The method used in this paper work is modeling, which exist in the most animal breeding scientifically papers. After the simulations, we observed that the most convenient variant was that which prefigure use of collateral selection and a maximum value for i/T ratio which can be obtained when average length of service is 5 years for females and 1 year for males.